Exploring Arabic Literature in Bahrain and Iran Region - Hariyani, Nety Novita (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2022)
The development of Arabic literature in Bahrain and Iran has apparent differences. This assumption aligns with the use of different languages in Bahrain and Iran regions, thus influencing the development of Arabic literature in the region. This study aims to (1) explore Arabic literature in Bahrain region, both in terms of the history of literary development and its figures, and (2) explore Arabic literature in Iranian region. The results (1) Arabic literature in Bahrain has developed in the last half-century. Bahrain has even become a pioneer in the Gulf countries in writing drama texts. Arabic literature in Bahrain region also pays attention to oral literature (folklore). Arab literary figures in Bahrain region include Ibrahim al-'Arrayyd, Qasim Haddad, and Ali Al-Sharqawi; (2) The development of Arabic literature in Iranian region is marked by the movement of translating literary texts from Arabic into Persian, for example, the translation of Jurji Zaydan's riwaya. Among the Iranian scholars who paid attention to Arabic literature were Professor Mulla Ahmad Al-Nodshi, Mulla Al-Baytoshi, Professor Burhan Al-Din Al-Hamdi, and Professor Baba Marduk Al-Ruhani.